Effects of foliar-sprayed bio-fertilizer with N-fixing Methylobacterium symbioticum on morpho-physiological traits of maize under varying N fertilization rates - Bolla, Pranay Kumar; Panozzo, Anna; Minozzi, Edoardo; Valente, Francesco; Potestio, Silvia; Visioli, Giovanna; Martinez-Sañudo, Isabel; Vamerali, Teofilo (Frontiers in Plant Science, 2025)
Nitrogen (N) fertilization remains a critical challenge in sustainable agriculture. Plant growth-promoting bacteria offer a promising strategy to enhance nitrogen use efficiency and improve cereal crop productivity while reducing reliance on synthetic inputs. This open-field study evaluated the morpho-physiological effects of foliar application of Methylobacterium symbioticum (MS) on maize in NE Italy. Following a baseline application of liquid digestate (300 kg N ha-¹) to all plots, four treatments were compared: N300 (digestate only, serving as the control); N300 + MS (digestate with MS); N350 (digestate with 50 kg ha-¹ chemical N); and N320 + MS (digestate with 20 kg ha-¹ chemical N and MS). ESEM imaging confirmed colonization of leaf surfaces by M. symbioticum. Its application significantly promoted aboveground growth and delayed leaf senescence by improving chlorophyll retention, increasing seasonal average SPAD from 46.9 in control to 49.4 (+5.3%, N300 + MS) and 48.8 (+4.1%, N320 + MS), likely mediated by the ascertained ACC-deaminase activity of MS. Root electrical capacitance showed treatment-specific effects, with the highest readings under the N320 + MS treatment (+54% vs. control at flowering). Yield responses were non-linear with respect to N dose, with N300 + MS showing a 12% (1,364 g/m²) and N320 + MS a 6% non-significant increase vs. control. MS-treated plants also exhibited a non-significant 5% increase in grain protein content, but significantly higher aboveground N accumulation. It is concluded that, this microbial inoculation strategy can enhance N use efficiency, particularly under reduced synthetic fertilization, presenting an environmentally-friendly and sustainable agricultural strategy for maize cultivation.